DIGITAL GOVERNANCE EFFECTIVENESS IN PUBLIC ORGANIZATIONS: A SYSTEMATIC LITERATURE REVIEW OF INSTITUTIONAL CAPACITY AND ORGANIZATIONAL CULTURE - Mustakim; Muhammad Nur Budiyanto; Raniasa Putra (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This article synthesizes evidence on the relationships among institutional capacity, organizational culture, and the effectiveness of digital governance in public organizations, its implications for the development of future empirical research in more specific contexts. The review was conducted in accordance with the PRISMA 2020 guidelines and employed an initial corpus of 2,623 bibliographic records drawn from 20 RIS files compiled from Google Scholar, Scopus, and ScienceDirect. After deduplication, 2,231 unique records remained. A staged screening process based on publication year, public organization context, digital governance relevance, and conceptual fit produced 134 metadata-based candidates, which were subsequently narrowed to 15 priority studies for full-text review. The synthesis indicates that institutional capacity is most operationalized through regulation, coordination, interoperability, civil servant competence, capability, and organizational adaptive capacity. Organizational culture functions as both an enabling and constraining condition, particularly through trust, digital leadership, collaboration, learning, and public values. Meanwhile, the effectiveness of digital governance is most consistently reflected in service quality, administrative efficiency, transparency, public trust, public value, and government effectiveness. Cross-study findings confirm that the effectiveness of digital governance cannot be understood as an automatic outcome of technology adoption; rather, it constitutes an organizational outcome shaped by the interaction between institutional readiness and organizational culture that supports change.